2021
DOI: 10.1021/acs.jpclett.1c02767
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Protein–Protein Conjugation through Internal Site Verified at the Single-Molecule Level

Abstract: Enzymes are widely used for protein ligation because of their efficient and site-specific connections under mild conditions. However, many enzymatic ligations are restricted to connections between protein termini while protein−protein conjugation at a specific internal site is limited. Previous work has found that Sortase A (SrtA) conjugates small molecules/peptides to a pilin protein at an internal lysine site via an isopeptide bond. Herein, we apply this noncanonical ligation property of SrtA for protein−pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Recent studies have shown that the C-terminal LPXTG acceptor motif works for not only N-terminal polyglycine motifs and primary amines but also an engineered internal sequence (YKPH) which opens the door to nonlinear protein−protein conjugates using sortase-based methods. 114 Finally, incorporation of a cysteine residue before the C-terminal sortase sequence tag enabled both protein−protein conjugation and protein− fluorophore conjugation. 115…”
Section: Enzymatic Methods and Tag Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the C-terminal LPXTG acceptor motif works for not only N-terminal polyglycine motifs and primary amines but also an engineered internal sequence (YKPH) which opens the door to nonlinear protein−protein conjugates using sortase-based methods. 114 Finally, incorporation of a cysteine residue before the C-terminal sortase sequence tag enabled both protein−protein conjugation and protein− fluorophore conjugation. 115…”
Section: Enzymatic Methods and Tag Engineeringmentioning
confidence: 99%
“…Sortase-based methods for preparing protein–protein conjugates are becoming some of the most widely applied, in particular for the addition of orthogonal functional groups that enable protein–protein conjugation via click chemistry. Recent studies have shown that the C-terminal LPXTG acceptor motif works for not only N-terminal polyglycine motifs and primary amines but also an engineered internal sequence (YKPH) which opens the door to nonlinear protein–protein conjugates using sortase-based methods . Finally, incorporation of a cysteine residue before the C-terminal sortase sequence tag enabled both protein–protein conjugation and protein–fluorophore conjugation …”
Section: Enzymatic Methods and Tag Engineeringmentioning
confidence: 99%
“…After release of the displaced C-terminus portion of the substrate protein, the transpeptidase activity then conjugates the N-terminus of a Gly-bearing protein/peptide to the electrophilic thioester displacing sortase A and forming a new amide bond to the carboxyl group of the Thr residue (Scheme ). Sortase A activity has been reported for ligation reactions and various applications including but not limited to covalent attachment of proteins onto solid supports, protein–protein ligation, peptide cyclization, and conjugation of small molecules to proteins. ,, The literature includes articles that present more detailed reviews of sortase-mediated ligations , and challenges in the use of sortase and other peptide ligases …”
Section: Fragment Crystallizable (Fc)-based Chemically Programmed Ant...mentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46] Thus, new methods generating site-specific and strong protein immobilization can be invaluable for obtaining reliable and efficient single-molecule results. [47][48][49][50][51][52] We demonstrated these two methods by immobilizing eGFP and studied its unfolding process by AFM-SMFS, both showing ideal results.…”
Section: Introductionmentioning
confidence: 99%